Alteration of pulmonary mitochondrial oxidation status, inflammation, energy metabolizing enzymes, oncogenic and apoptotic markers in mice model of diisononyl phthalate-induced asthma - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Akinpelu , Oyindamola Joy; Ogunsanya , Sanmi Tunde (Life Sciences, Medicine and Biomedicine, 2023)
Primary plasticizer used in polyvinyl chloride is diisononyl phthalate (DiNP) and exposure to  DiNP has been associated with the development of asthma and allergies. In the current study,  how DiNP alters pulmonary antioxidant status, inflammation, energy metabolizing enzymes,  oncogenic and apoptotic markers in DiNP-induced asthmatic mice was examined. Male  BALB/c mice (n=20, 20-30 g) were divided into 2 groups of 10 mice each: group 1 (control)  received saline (0.2ml/kg) orally for 23 days, and group 2 (DiNP) received 50 mg/kg DiNP  (Intraperitoneal and intranasal) once per day. After the last administration, mice were sacrificed, lungs were removed and used for biochemical and histopathological analysis. DiNP treated mice experienced alterations in their lung histoarchitecture, levels of oncogenic and  apoptotic factors, glycolytic, tricarboxylic acid cycle (TCA), and electron transport chain  enzymes (ETC), antioxidant status, and inflammatory biomarkers. DiNP decreased the  lungs levels of reduced glutathione and ascorbic acid, and the activities of  superoxide dismutase, catalase, and glutathione-s-transferase. In the lungs  of DiNP-treated mice compared to the control group, malondialdehyde and  inflammatory biomarkers (nitric oxide and myeloperoxidase) were significantly  greater (p